The Importance of Serve and Return in the Infant Classroom Settings (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2018)
The aim of this article is to explore the importance of early childhood education focusing on infant care by using serve and return, which is undeniably one of the most important components of infant education. It is a proven fact, that healthy relationships between children and their caregivers are extremely important for developing a strong brain. Starting with infancy, the bond between children and their caregivers builds a strong foundation for development focusing on serve – and – return interactions. Babies are extremely responsive to emotions, reactions to activities and social interactions that they receive from the world around them.